2016
DOI: 10.3233/jad-160189
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Stress Aggravates Cognitive Impairment and Suppresses Insulin Associated Signaling Pathway in APP/PS1 Mice

Abstract: Differences in brain function are a central determinant of individual variability in the stress response. Brain dysfunction, resulting from aging, illness, or genetic mutations, could reduce the tolerance of glucocorticoid stress hormones. When glucocorticoids exceed tolerable limits in the brain, especially in the hippocampus, this state can cause or aggravate structural or functional damage. However, the underlying mechanisms are not well understood. This study investigated the effects of chronic unpredictab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
27
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 52 publications
5
27
0
Order By: Relevance
“…Chronic stress not only impaired the early long- term potentiation (LTP) in the at-risk rat model of AD [9], but it also decreased hippocampal synaptic plasticity [10] and increased amyloid-β plaque deposition in Tg2576 mice [11]. Furthermore, our previous study also confirmed that chronic stress exposure increased the levels of glucocorticoids (1.5-fold), promoted senile plaque deposition, neuronal injury, and cognitive impairment in APP/PS1 mice compared to wild-type mice [12]; however, the cognition-related metabolic mechanisms during chronic stress are not well understood.…”
Section: Introductionsupporting
confidence: 58%
See 2 more Smart Citations
“…Chronic stress not only impaired the early long- term potentiation (LTP) in the at-risk rat model of AD [9], but it also decreased hippocampal synaptic plasticity [10] and increased amyloid-β plaque deposition in Tg2576 mice [11]. Furthermore, our previous study also confirmed that chronic stress exposure increased the levels of glucocorticoids (1.5-fold), promoted senile plaque deposition, neuronal injury, and cognitive impairment in APP/PS1 mice compared to wild-type mice [12]; however, the cognition-related metabolic mechanisms during chronic stress are not well understood.…”
Section: Introductionsupporting
confidence: 58%
“…There is evidence that stress or excessive glucocorticoids, once beyond the tolerable limit, have deleterious effects on brain structure and function; more severe damage may occur in some vulnerable groups, e.g., AD patients[11, 12, 43]. However, few studies have focused on the metabolic pattern in AD during chronic stress.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These unexpected results suggest that the availability of adiponectin receptors can be stabilized even in cases where genetic and environmental risk factors for AD co-occur. Recently, Han et al (2016) demonstrated that insulin receptor levels are decreased in the hippocampus of AD mice and can further decline after stress exposure, concluding that people with harmful genetic mutations are more likely to be vulnerable to stress. Further investigation is necessary to explore the mechanism to explain the difference between the stress-induced changes of adiponectin and insulin receptors.…”
Section: Discussionmentioning
confidence: 99%
“…Repeated stress has been implicated in the pathogenesis of diverse diseases, which ranges from anxiety, depression, posttraumatic stress disorder, and cognitive dysfunction (Henn and Vollmayr, ; Cordner and Tamashiro, ; Han et al, ; Yu et al, ). Several studies have reported that chronic stress impairs spatial learning and memory (McEwen, ; Srikumar et al, ; Ramkumar et al, ; Veena et al, ; Cordner and Tamashiro, ; Han et al, ; Yu et al, ). Indeed, repeated stress results in morphological, cellular, and electrophysiological changes in the hippocampus.…”
mentioning
confidence: 99%